3R EVOKES ECODESIGN IDENTITY IN ECOLOGICAL SYSTEM OF GREEN MANUFACTURING - Chumiran, Mohd Hasni; Abidin, Shahriman Zainal; Anwar, Rusmadiah; Vermol, Verly Veto; Sirat, Anuar (International Journal of Supply Chain Management, 2020)
For the past few decades to the era of industry 4.0, young practising designers have been enduring environmental communication challenges in the green manufacturing context. The problems stem from their failure to comprehend the pattern of environment communication phenomenally. The objective of this study is to address the environmentally-driven elements of recycling methodology along with the productâ??s form development via â??re-think wasteâ? of the environmental communications concept; screened by the bubbling model of intangible ecological form theory. In the realm of industrial design, it is implicitly visualised by the common Mobius loop cycle method of the green manufacturing paradigm. Under the Descriptive Study I of design research methodology framework, the goal-setting participation from Malaysian manufacturers sample using two methodologies concurrently; (1) the cluster sampling that measured the designs perception as the quantitative structure by statistic values and (2) the purposive sampling interpreted the design behaviors of the subject as the qualitative structure by first cycle coding. Consequently, the heuristic evaluation is used to triangulate the two methodologies. For the finding, an intangible ecological form model formulated the change for environmental communication to digitise and screen an intangible ecological form according to extrapolative strategy morphing.